CRITICAL LINGUISTIC LANDSCAPE STUDIES: AN ALTERNATIVE CONCEPT TO CRITICAL DISCOURSE (KAJIAN LANSKAP LINGUISTIK KRITIS: SEBUAH KONSEP ALTERNATIF UNTUK WACANA KRITIS) - Yendra Yendra; Syairal Fahmy Dalimunthe; Nofel Nofiadri (Jurnal Gramatika, 2021)
In the latest decade sociolinguistics scholars have developed a special field of study that concerned to the use of language in public spaces, called linguistic landscape (LL). Many scholars believe research on LL still requires a lot of theoretical and methodological development because LL field varied, complex, rapidly developing and there are shifts between different idea settings. As a consequence LL became highly inter-disciplinary research domain which dealt with written signs in public spaces from many different perspective. This article propose critical linguistic landscape studies as an alternative concept aimed to examining the using of language sign in public spaces, particularly concern in the study of critical discourse. This concept is unique because moving on beyond the tendency of many earlier LL works which still trapped in the distributional level of analysis language sign in public space, so that this LL studies need seeks to enter productive aspects of using language signs in public space as a text at interpretative level. This is library research which is designed as descriptive qualitative study, as well-known as theoretical review. The technique used in exploring the ideas is comparative material base on early work of LL studies. The primary sources of this study are research reports, journals, books and other scientific papers discussed about LL, that represent original thinking